Compostos bioativos na qualidade fisiológica e sanitária de diásporos de Myracrodruon urundeuva Fr. All. - Senigalia, Ritielly Laiany Carvalho (2018)
Myracrodruon urundeuva Fr. All. is a species that has high potential to be used in the recovery of degraded areas. Due to the environmental compensations, aiming the recomposition of the native flora, the interest in the propagation of this species has been increasing. Seed quality interferes with propagation and due to the large number of pathogens associated with M. urundeuva diaspores and studies on control methods are important. The objective of this work was to evaluate the physiological and sanitary quality of M. urundeuva diaspores treated with plant extracts and essential oils. Thus, two experiments were carried out in a completely randomized experimental design. In the experiment I, aqueous extracts of Syzygium aromaticum, Cinnamomum zeylanicum, Strychnos pseudoquina, Cymbopogon citratus and Allium sativum were used in the concentrations of 0, 25, 50, 75 and 100%. In the experiment II, essential oils S. aromaticum, C. zeylanicum, Citrus sinensis and Melaleuca alternifolia were used at concentrations of 0; 1.25; 2.5; 3.75 and 5 mL kg-1 and the diaspores in both experiments were stored for 180 days. As a positive control, the chemical fungicide Carboxina+Thiram a 2,5 mL kg-1 was used. Germination tests (%), germination speed index, electrical conductivity (μS cm g-1), hypocotyl length and main root (cm) and pathogen incidence (%) were performed every 30 days. The data were submitted to analysis of main components, with different times for sanitary quality, analysis of variance, polynomial regression and calculation of the area below the disease progress curve (AACPD). The compounds used did not differ from the chemical fungicide in the control of fungal infection and increased the physiological quality of the diaspores in relation to the control and the oils reduced the vigor, but all caused toxicity on M. urundeuva diaspore mycoflora and can be used as alternative to synthetic pesticides.